Feedback and Governance Capacity in Indonesia's Tobacco Excise Policy: The Role of Narrative Coalitions - Aris Munandar; Alfitri Alfitri; M. Husni Thamrin; Alamsyah Alamsyah (Jurnal Administrasi Publik (Public Administration Journal), 2026)
This study looks at policy feedback as a factor that influences the governance capacity in Indonesia’s tobacco excise policy. While previous studies have explored fiscal performance, economic implications and public health consequences, there has been limited attention on how excise policy affects governance in the post-implementation stage. This study addresses the gap by examining structural, interpretive and behavioural feedbacks and the role of narrative coalitions in the development of policy legitimacy. An embedded mixed-methods design was employed using policy documents, media coverage, academic literature, and a survey of 100 tobacco consumers. Qualitative data were analysed through open, axial, and selective coding, while survey data were analysed descriptively. The findings show that structural feedback reinforces fiscal-administrative routines more strongly than public-health objectives. Interpretive feedback reveals competing health, economic-security and cultural-identity narratives that affect policy legitimacy. Many smokers reacted to excise increases with consumption changes, product switching, and rolling-your-own tobacco rather than cessation. Drawing on policy feedback theory, this study shows how governance capacity is built through the interaction of institutions, narratives and citizen adaptation. This study provides a governance-based explanation of tobacco excise policy by combining structural, interpretive and behavioral feedback within a common analytical framework.